Bone morphogenetic protein and Notch signalling crosstalk in poor-prognosis, mesenchymal-subtype colorectal cancer. - Irshad, S; Bansal, M; Guarnieri, P; Davis, H; Al Haj Zen, A; Baran, B; Pinna, C; Rahman, H; Biswas, S; Bardella, C; Jeffery, R; Wang, L; et al. (Wiley, 2017)
The functional role of bone morphogenetic protein (BMP) signalling in colorectal cancer (CRC) is poorly defined, with contradictory results in cancer cell line models reflecting the inherent difficulties of assessing a signalling pathway that is context-dependent and subject to genetic constraints. By assessing the transcriptional response of a diploid human colonic epithelial cell line to BMP ligand stimulation, we generated a prognostic BMP signalling signature, which was applied to multiple CRC datasets to investigate BMP heterogeneity across CRC molecular subtypes. We linked BMP and Notch signalling pathway activity and function in human colonic epithelial cells, and normal and neoplastic tissue. BMP induced Notch through a γ-secretase-independent interaction, regulated by the SMAD proteins. In homeostasis, BMP/Notch co-localization was restricted to cells at the top of the intestinal crypt, with more widespread interaction in some human CRC samples. BMP signalling was downregulated in the majority of CRCs, but was conserved specifically in mesenchymal-subtype tumours, where it interacts with Notch to induce an epithelial-mesenchymal transition (EMT) phenotype. In intestinal homeostasis, BMP-Notch pathway crosstalk is restricted to differentiating cells through stringent pathway segregation. Conserved BMP activity and loss of signalling stringency in mesenchymal-subtype tumours promotes a synergistic BMP-Notch interaction, and this correlates with poor patient prognosis. BMP signalling heterogeneity across CRC subtypes and cell lines can account for previous experimental contradictions. Crosstalk between the BMP and Notch pathways will render mesenchymal-subtype CRC insensitive to γ-secretase inhibition unless BMP activation is concomitantly addressed.